IMPLEMENTASI FUNGSI MANAJEMEN DAKWAH DALAM KEGIATAN KEAGAMAAN DI MESJID AL-MUSANNIF JALAN CEMARA - Asari, Syafna; Azhar (Kodifikasia, 2025)
This study examines the application of da'wah management in religious activities at the Al-Musannif Cemara Mosque which is under the auspices of the Haji Anif Foundation. The research method used is a qualitative approach. Data collection techniques through observation and interviews. The results showed that da'wah management at Al-Musannif Mosque is carried out professionally and structured. Various routine religious activities such as daily recitation, rice distribution for the poor, as well as major annual activities such as the commemoration of Haul H. Anif and Musabaqoh Tilawatil Qur'an (MTQ) Haji Anif Foundation run consistently and continuously. The implementation of da'wah management functions includes planning based on identifying the needs of the congregation, deliberation, and determining well-documented resources. Organizing is done through a clear work structure with the division of tasks according to the type of activity and the competence of the management. Implementation of activities according to schedule with the active involvement of administrators and worshipers. Control and evaluation are carried out regularly through direct monitoring and collecting input from worshipers. The function of da'wah management has been implemented effectively, which is reflected in the smooth implementation of activities and positive responses from worshipers. However, the aspects of evaluation and documentation can still be improved so that the management of da'wah is more optimal in the future.